Ochratoxin A triggered intracerebral hemorrhage in embryonic zebrafish: Involvement of microRNA-731 and prolactin receptor. (March 2020) - Wu, Ting-Shuan; Lin, Yu-Ting; Huang, Ying-Tzu; Yu, Feng-Yih; Liu, Biing-Hui
Abstract: Ochratoxin A (OTA), a mycotoxin widely found in foodstuffs, reportedly damages multiple brain regions in developing rodents, but the corresponding mechanisms have not been elucidated. In this study, zebrafish embryos at 6 h post fertilization (hpf) were exposed to various concentrations of OTA and the phenomenon associated with intracerebral hemorrhage was observed at 72 hpf. Exposure of embryos to OTA significantly increased their hemorrhagic rate in a dose-dependent manner. Large numbers of extravagated erythrocytes were observed in the midbrain/hindbrain areas of Tg(fli-1a:EGFP; gata1:DsRed) embryos following exposure to OTA. OTA also disrupted the vascular patterning, especially the arch-shaped central arteries (CtAs), in treated embryos. Histological analysis revealed a cavity-like pattern in their hindbrain ventricles, implying the possibility of cerebral edema. OTA-induced intracerebral hemorrhage and CtA vessel defects were partially reversed by the presence of miR-731 antagomir or the overexpression of prolactin receptor a ( prlra ); prlra is a downstream target of miR-731. These results suggest that exposure to OTA has a negative effect on cerebral vasculature development by interfering with the miR-731/PRLR axis in zebrafish. Graphical abstract: Image 1 Highlights: OTA induced intracerebral hemorrhage (ICH) in embryonic zebrafish. OTA interfered with the development of cerebral vasculature. The formation of central arteries (CtAs) was adversely affected by OTA. The miR-731/PRLRa axis involved in OTA-induced vascular defects and led to ICH.